2018
DOI: 10.3390/ijms19041261
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Expression and Macrophage Localization in Xenograft and Allograft Tumor Models Stimulated with Lipopolysaccharide

Abstract: T cell-deficient mice such as nude mice are often used to generate tumor xenograft for the development of anticancer agents. However, the functionality of the other immune cells including macrophages, dendritic cells (DCs), and myeloid-derived suppressor cells (MDSCs) in the xenograft are largely unknown. Macrophages and dendritic cells (DCs) acquire functionally distinct properties in response to various environmental stimuli; the interaction of these cells with MDSCs in tumor microenvironments regulates canc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 36 publications
(46 reference statements)
2
15
0
Order By: Relevance
“…The high H 2 S treatment even further increased the intensity of the monocyte and macrophage staining with a fold change of 4.2 ± 0.5. In addition, the literature states that nude mice have an exaggerated macrophage response [16]. In accordance with the literature, we observed a higher number of MOMA-2 positive pixels per mm 2 of scaffold, 223,358 ± 71,364 and 72,532 ± 31,919, in the nude mice of the control groups compared to the C57BL/6 mice, respectively ( Figure S1B).…”
Section: Genesupporting
confidence: 91%
“…The high H 2 S treatment even further increased the intensity of the monocyte and macrophage staining with a fold change of 4.2 ± 0.5. In addition, the literature states that nude mice have an exaggerated macrophage response [16]. In accordance with the literature, we observed a higher number of MOMA-2 positive pixels per mm 2 of scaffold, 223,358 ± 71,364 and 72,532 ± 31,919, in the nude mice of the control groups compared to the C57BL/6 mice, respectively ( Figure S1B).…”
Section: Genesupporting
confidence: 91%
“…Given the protective effect of STDME against CAC, we next examined the accumulation of MDSCs in the spleen. MDSCs were identified as two populations by the co-expression of the myeloid lineage differentiation antigens Gr-1 and CD11b [ 9 , 30 , 32 ]. The percentages of Gr-1 dim CD11b + and Gr-1 hi CD11b + MDSCs in STDME-fed mice were significantly lower than those in the control group ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Since MDSCs are myeloid precursors that expand during chronic inflammation and tumor growth, the accumulation of splenic MDSCs is observed in cancer model ( Figure 3 ). MDSCs inhibit both adaptive and innate immunity through a variety of diverse mechanisms [ 9 , 30 , 37 ]. MDSCs that accumulate during tumor growth increase ROS production [ 38 ] and increased ROS suppresses antigen-specific activation of T cells [ 37 , 39 ] and differentiation of MDSCs into mature myeloid cells such as tumoricidal M1-like macrophages [ 37 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, according to our previous results, the tumor-suppressive effect of ASCs cultured at a high density in the xenograft tumor model using athymic nude mice was not significant [25]. Moreover, although it has been reported that the function of macrophages and DCs is maintained in xenograft tumor models using athymic nude mice [55], it remains controversial whether the distribution and function of macrophages and DCs in the tumor microenvironment is normal. However, the current study demonstrated that in the colitis-associated cancer model, ASCs modulated the macrophage population during colon cancer development.…”
Section: Discussionmentioning
confidence: 77%